Sofía is leaving the school. (Journal of Parents and Teachers, 2025)
The article refers to a best-seller about the book *Sofía Leaves School*, which in this case deals with learning, philosophical systems, formulations, adventures, and human experiences developed by the students. It also presents a series of questions and answers, covering topics such as happiness, the scientific method, criticism of philosophy, freedom...